Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jssc.201700593
|View full text |Cite
|
Sign up to set email alerts
|

Single standard substance for the determination of nine volatile components in the distillate of Fructus Gardeniae and Radix Curcumae (an intermediate of Xingnaojing Injection)

Abstract: Xingnaojing Injection is a traditional Chinese medicine extensively used for stroke and cerebral ischemia. For better in-process quality control of Xingnaojing Injection, a method for the analysis of its intermediate (i.e., the distillate of Fructus Gardeniae and Radix Curcumae) is needed to monitor and optimize the hydrodistillation extraction process. In this work, nine major volatile components in the intermediate were identified: isophorone, 4-methylene-isophorone, curcumenone, curcumenol, curdione, curzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Rhizome of various Curcuma species, a rich source of curcumol, serves as antimicrobial, antifibrotic, and anticancer agent [32][33][34]. Besides them, curcumol has also been isolated from the roots of Astragali radix, C. rhizoma, and Fructus gardenia which are traditionally used as anticancer agents [35,36].…”
Section: Curcumol and Its Natural Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizome of various Curcuma species, a rich source of curcumol, serves as antimicrobial, antifibrotic, and anticancer agent [32][33][34]. Besides them, curcumol has also been isolated from the roots of Astragali radix, C. rhizoma, and Fructus gardenia which are traditionally used as anticancer agents [35,36].…”
Section: Curcumol and Its Natural Sourcesmentioning
confidence: 99%
“…The summary of plants containing curcumol and biological activities are enlisted in Table 1. Figure 1 provides natural sources of curcumol including Astragali radix [36], C. aeruginosae [20], C. aromatica [21], C. kwangsiensis [22], C. longa [37], C. phaeocaulis [24], C. wenyujin [38], C. zedoary [28], Fructus gardenia [35], and C. trichosantha G. [39].…”
Section: Curcumol and Its Natural Sourcesmentioning
confidence: 99%
“…The concentrations of the five compounds of interest in the distillate were determined by high-performance liquid chromatography analysis (Fang et al, 2017), which was carried out on Waters e2695 …”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%
“…The concentrations of the five compounds of interest in the distillate were determined by high-performance liquid chromatography analysis (Fang et al, 2017), which was carried out on Waters e2695 Six mixed standard solutions were used as the calibration series, in which the concentrations were 18.1, 7.24, 3.62, 1.81, 0.724 and 0.362 lg mL À1 for curcumenone, 62.6, 25.0, 12.5, 6.26, 2.50 and 1.25 lg mL À1 for curcumenol, 81.2, 32.5, 16.2, 8.12, 3.25 and 1.62 lg mL À1 for curdione, 49.5, 19.8, 9.91, 4.95, 1.98 and 0.991 lg mL À1 for curzerenone, and 24.0, 9.60, 4.80, 2.40, 0.960 and 0.480 lg mL À1 for furanodienone, respectively.…”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%
“…Although several methods have been developed for analysis of furanodienone in plant extracts (Fang, Yang, Ge, Bai, & Yan, 2017;Yang et al, 2005;Yang, Li, Zhao, Lao, & Wang, 2007;Yang, Wang, & Li, 2006;Yin et al, 2018), limitations to these methods still preclude their implementation in pharmacokinetic studies. Yang et al and Fang et al reported a high-performance liquid chromatography-photodiode array for the determination of furanodienone along with other compounds with a limit of quantiation (LOQ) of 1.92-2.72 ng (Fang et al, 2017;Yang et al, 2006), and this method, owing to its poor selectivity and long run times (40 min), is not a high-throughput bioanalysis of furanodienone. Yang et al developed a gas chromatography-mass spectrometry method for simultaneous determination of nine sesquiterpenoids in three species of Curcuma rhizomes (Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%